2019
DOI: 10.3847/2041-8213/ab53eb
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Neutron Star Mass–Radius Relation and Dense Matter Equation of State with NICER. I. The Millisecond Pulsar X-Ray Data Set

Abstract: We present the set of deep Neutron Star Interior Composition Explorer (NICER) X-ray timing observations of the nearby rotation-powered millisecond pulsars PSRs J0437−4715, J0030+0451, J1231−1411, and J2124−3358, selected as targets for constraining the mass-radius relation of neutron stars and the dense matter equation of state via modeling of their pulsed thermal X-ray emission. We describe the instrument, observations, and data processing/reduction procedures, as well as the series of investigations conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 104 publications
3
115
0
1
Order By: Relevance
“…These masses are consis-tent with astrophysical observations of NSs (see e.g. [13][14][15][16]), but it cannot rule out the presence of a stellar-mass BH [17]. Recently, X-ray observations have strongly suggested that the rapidly rotating, giant star 2MASS J05215658+4359220 is the binary companion of a noninteracting ∼ 3M BH [18].…”
Section: Introductionmentioning
confidence: 54%
“…These masses are consis-tent with astrophysical observations of NSs (see e.g. [13][14][15][16]), but it cannot rule out the presence of a stellar-mass BH [17]. Recently, X-ray observations have strongly suggested that the rapidly rotating, giant star 2MASS J05215658+4359220 is the binary companion of a noninteracting ∼ 3M BH [18].…”
Section: Introductionmentioning
confidence: 54%
“…The NICERXTI data set d associated with the rotationpowered MSP PSRJ0030+0451 is necessarily a product of pre-processing, and its curation is largely described in Bogdanov et al (2019a). However, there are a number of details that are specific to each data set and so we record a summary of these details below.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…The raw XTI event data are publicly available via the NICER archive (accessible via HEASARC 27 ). The processed data set d may be found in the persistent repository of Bogdanov et al (2019c).…”
Section: Data Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations